Short term negative effect of oxalic acid in Apis mellifera iberiensis - Martín Hernández, R; Higes, M; Pérez, J.L.,Junta de Comunidades de Castilla-La Mancha, Marchamalo, Guadalajara (España). Centro Apícola Regional; Nozal, M.J; Gómez, L; Meana, A (Spanish journal of agricultural research : SJAR, 2007)
En este trabajo se demuestra el efecto tóxico de la aplicación de ácido oxálico (AO) en Apis mellifera iberiensis en ensayos de campo y de laboratorio. La mortalidad de las abejas fue mayor en las colmenas tratadas frente a los grupos controles. Se observaron lesiones patológicas en diferentes órganos internos tras la administración tópica de AO al 10%. A las 24 h de la administración, las lesiones fueron graves en el epitelio del ventrículo, mientras que a las 48 h también pudo observarse la degeneración epitelial en el recto. El efecto tóxico del AO continúa tras el contacto inicial y es capaz de producir lesiones permanentes en el aparato digestivo y excretor. La distribución tisular del AO tras la aplicación tópica señala que parte se ingiere por la abeja, quizás en el proceso de autolimpieza. The toxic effect of oxalic acid (OA) on Apis mellifera iberiensis was studied using field and laboratory assays. Bee deaths were higher in OA treated hives than in control hives. Pathological repercussions of topical application of 10% OA were observed in different internal honeybee organs. After 24 h, there were severe alterations in the ventricular epithelial layer while by 48 h there was clearly seen degeneration of the rectal epithelium. Irreversible lesions appeared at 48 h in different bee organs with increased cellular damage after 72 h. Indications are that the effect of the OA continues after initial contact and causes permanent lesions in digestive and excretory organs. Tissue distribution of the acid in different bee organs, after topical administration, suggests that some of the acid is ingested, in some way, by the bee.